Attenuated levels of pro-inflammatory markers in diabetic retinopathy patients undergoing treatment with antihyperglycemic and antihypertensive drugs - Ng, Z.X.; Chua, K.H.; Tajunisah, I.; Pendek, R.; Kuppusamy, U.R. (2013)
OBJECTIVE: This study aimed to assess the circulating levels of activated nuclear factor kappa B p65 and monocyte chemotactic protein-1 in diabetic retinopathy patients who were taking antihyperglycemic and antihypertensive drugs. METHODS: In total, 235 healthy controls and 371 Type 2 diabetic patients 171 without retinopathy (DNR) and 200 patients with retinopathy (diabetic retinopathy) were recruited for this study. Plasma and the nuclear fraction of peripheral blood mononuclear cells were isolated for the quantification of the monocyte chemotactic protein-1 and nuclear factor kappa B p65 levels, respectively. RESULTS: Non-medicated diabetic retinopathy patients had significantly higher levels of activated nuclear factor kappa B p65 and plasma monocyte chemotactic protein-1 than DNR patients. Diabetic retinopathy patients who were taking antihyperglycemic and antihypertensive drugs showed significant reductions in both the nuclear factor kappa B p65 and monocyte chemotactic protein-1 levels compared with the non-medicated patients. CONCLUSION: This study demonstrated the significant attenuation of both the nuclear factor kappa B p65 and circulating monocyte chemotactic protein-1 levels in diabetic retinopathy patients taking antihyperglycemic and antihypertensive drugs.